2019
DOI: 10.1371/journal.pone.0211783
|View full text |Cite
|
Sign up to set email alerts
|

Economic benefits of subcutaneous trastuzumab administration: A single institutional study from Karolinska University Hospital in Sweden

Abstract: IntroductionAdjuvant trastuzumab is a standard of care in the treatment of Human Epidermal growth factor Receptor 2 (HER2) positive early breast cancer (eBC). Initially trastuzumab could only be administered intravenously (IV), however since 2013, a subcutaneous (SC) formulation with comparable efficacy and safety profile is available and preferred by patients. Trastuzumab SC does not require pharmacy preparation and has shorter administration time. The objective of this study was to estimate the economic effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Several studies report that costs for non-drug consumables can further reduce overall costs associated with H SC injection compared with IV infusion [ 13 , 16 , 20 , 21 ]. Moreover, a Swedish study [ 15 ] reported significant H SC central venous access device (CVAD)-related cost savings, i.e., direct monetary cost savings from avoiding the need for surgery to implant port-a-caths, which can be otherwise required for patients newly diagnosed with early breast cancer and receiving IV infusions.…”
Section: Value Of Ph Fdc Sc To Patients and Healthcare Professionalsmentioning
confidence: 99%
“…Several studies report that costs for non-drug consumables can further reduce overall costs associated with H SC injection compared with IV infusion [ 13 , 16 , 20 , 21 ]. Moreover, a Swedish study [ 15 ] reported significant H SC central venous access device (CVAD)-related cost savings, i.e., direct monetary cost savings from avoiding the need for surgery to implant port-a-caths, which can be otherwise required for patients newly diagnosed with early breast cancer and receiving IV infusions.…”
Section: Value Of Ph Fdc Sc To Patients and Healthcare Professionalsmentioning
confidence: 99%
“…5 Subcutaneous (SC) delivery as an alternative to IV infusion is of increasing interest as it provides expanded opportunity for self-or caregiver-assisted administration at home or in an office setting (using devices such as prefilled syringes, autoinjectors, wearable bolus injectors and pumps) and reduces the frequency of or eliminates hospital visits, thereby improving patient experience and increasing patient compliance, [6][7][8][9] reducing patient and caregiver treatment burden, and lowering treatment costs and healthcare resource utilization. [10][11][12][13][14][15][16][17][18][19] Additionally, there are a number of reports available in the literature that indicate switching to SC administration may reduce instances of infusion-related reactions often associated with IV infusions. [20][21][22] Other promising patient-centric approaches that have been studied for sub/transcutaneous self-administration of biologics include microneedles, 23,24 microneedle patches, 25 jet/needlefree injections, 26 and SC implants.…”
Section: Introductionmentioning
confidence: 99%
“…This shift should provide for preference-based selection of Herceptin over biosimilar products, as supported by data from prefHER study (ClinicalTrials.gov Identifier: NCT01401166), in which 86% of patients preferred subcutaneous Herceptin over intravenous administration. [36][37][38] Anti-ErbB2 investigational products…”
Section: Trastuzumab Biosimilarsmentioning
confidence: 99%